The correction of program trajectories of industrial robots’ end effectors movement subject to obstacles avoiding - Богдановський, Мартін Віталійович; Кирилович, Валерій Анатолійович (Eastern-European Journal of Enterprise Technologies, 2011)
The general genetic algorithm of program trajectory key points for obstacles avoiding task is considered in this paper. The dynamics of industrial robots manipulation system movements is allow for the adaptation and fitness functions which include the dynamics of industrial robots manipulation system movements